THE IMPACT OF EDUCATION ON STUDENTS’ ENTREPRENEUR-IAL INTENTION. MUCH ADO ABOUT NOTHING OR TRUE CHANCE? - Ferri, Luca; Maffei, Marco; Spagnuolo, Flavio; Spanò, Rosanna (Piccola Impresa / Small Business, 2025)
Purpose. Rooted in the rationale that entrepreneurship can be taught and learned, this study aims to understand whether and how certain dimensions of students’ education affect their entrepreneurial intention (EI). Design/methodology/approach. Under the lens of Ajzen’s Theory of Planned Behavior (TPB), we employ structural equation modeling (SEM) on data gathered via Likert-based questionnaires to understand if attitudes, subjective norms, self-efficacy and students’ skills impact the EI in a sample of 1,730 graduate and undergraduate students across France, Italy, Lithuania, Poland and Spain. Findings. While the findings confirm that these factors can shape students’ EI, they also reveal that skills provided by universities are the most prominent element leading European students toward entrepreneurial careers. Also, we conducted an additional analysis to understand whether country differences affect our results, suggesting novel insights on the topic. Practical and social implications. The research contributes to academic discourse and policy considerations surrounding entrepreneurship, education, and training. Specifically, the paper advocates for rethinking the employment-education interface, offering practical tools and theoretical ideas to bridge the gap between entrepreneurial practice and higher education systems. Originality. By incorporating in the core of the analysis the role of skills acquired through university programs, the study offers a timely and comprehensive investigation of the factors influencing students’ entrepreneurial intention, contributing to a deeper understanding of their potential determinants.